2016
DOI: 10.3928/23258160-20151214-03
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Involvement in Acute Posterior Multifocal Placoid Pigment Epitheliopathy

Abstract: These results suggest a transient ischemic choroiditis in APMPPE that may lead to secondary permanent retinal pigment epithelium damage in the posterior pole but not in the retinal periphery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 14 publications
7
30
0
Order By: Relevance
“…OCTA is of great importance in revealing that within the corresponding hypofluorescent spots of ICGA, the choriocapillaris and retinal capillary blood flow are completely normal. This reinforces the concept that choriocapillaris may not be involved in this disease and the primary cause of it stands at the level of RPEphotoreceptor complex [1,23,[47][48][49] Acute posterior multifocal placoid pigment epitheliopathy FFA demonstrates early hypofluorescence of the acute posterior multifocal placoid pigment epitheliopathy (APMPPE) lesions and late hyperfluorescence due to staining [50][51][52]. APMPPE has been proposed to be a result of ischemia and acute inflammation of the choriocapillaris, but not of the medium and large sized choroidal vessels, leading to RPE abnormalities [53][54][55].…”
Section: Oct-a In Choroiditis (Choriocapillaropathies and Stromal Chosupporting
confidence: 79%
See 2 more Smart Citations
“…OCTA is of great importance in revealing that within the corresponding hypofluorescent spots of ICGA, the choriocapillaris and retinal capillary blood flow are completely normal. This reinforces the concept that choriocapillaris may not be involved in this disease and the primary cause of it stands at the level of RPEphotoreceptor complex [1,23,[47][48][49] Acute posterior multifocal placoid pigment epitheliopathy FFA demonstrates early hypofluorescence of the acute posterior multifocal placoid pigment epitheliopathy (APMPPE) lesions and late hyperfluorescence due to staining [50][51][52]. APMPPE has been proposed to be a result of ischemia and acute inflammation of the choriocapillaris, but not of the medium and large sized choroidal vessels, leading to RPE abnormalities [53][54][55].…”
Section: Oct-a In Choroiditis (Choriocapillaropathies and Stromal Chosupporting
confidence: 79%
“…This inner choroidal involvement as prominent feature is supported by the ICGA findings of hypofluorescent areas corresponding to the lesions observed on FFA [51,52,56,57]. OCT imaging manifests increased inner choroidal hyporeflectivity or lucency [52,58], ellipsoid zone disruption and sub-RPE drusenoid abnormalities with RPE atrophy ensuing in the course of the disease, all of which co-localize with the primary zone of choroidal hypoperfusion [1,59]. OCTA imaging confirmed that hypothesis of inner choroidal or choriocapillaris flow reduction, as it illustrates true choriocapillaris flow-void areas that correspond to the ICGA hypofluorescent spots and are of the same or larger size.…”
Section: Oct-a In Choroiditis (Choriocapillaropathies and Stromal Chosupporting
confidence: 67%
See 1 more Smart Citation
“…The ability to visualize large choroidal vessels on ICGA in areas of acute lesions make the possibility of blocked cyanescence by the RPE less likely and support the second theory. Subacute lesions with choroidal flow deficits on FA without structural OCT or autofluorescence findings have been previously identified, most recently by Mrejen et al 21 Furthermore, an incomplete overlap between acute lesions and areas of hypo-autofluorescence (and RPE changes) provides further evidence for a primarily choroidal disease. However, inconsistencies remain in the interpretation of the ICGA findings including the lack of correlation between the hypocyanescence and choroidal anatomy.…”
Section: Discussionmentioning
confidence: 80%
“…Controversy has persisted regarding the pathogenesis of APMPPE since its initial description by Gass [ 21 ], who chose the term “pigment epitheliopathy” to reflect the most significant clinical tissue involvement. However, the advent of ICGA in the 1990s has provided additional insights into APMPPE and has supported choroidal involvement as a prominent feature [ 22 ]. Still, several features of APMPPE remained atypical for a choroiditis including the rapid resolution of lesions and the near absence of damage to the choroid despite significant permanent alternations in the RPE.…”
Section: Reviewmentioning
confidence: 99%